Engineering nanomedicines through boosting immunogenic cell death for improved cancer immunotherapy - Gao Jing; Wang Wei-qi; Pei Qing; Lord Megan S.; Yu Hai-jun (Acta Pharmacologica Sinica, 2020)
Current cancer immunotherapy has limited response rates in a large variety of solid tumors partly due to the low immunogenicity of the tumor cells and the immunosuppressive tumor microenvironment (ITM). A number of clinical cancer treatment modalities, including radiotherapy, chemotherapy, photothermal and photodynamic therapy, have been shown to elicit immunogenicity by inducing immunogenic cell death (ICD). However, ICD-based immunotherapy is restricted by the ITM limiting its efficacy in eliciting a long-term antitumor immune response, and by severe systemic toxicity. To address these challenges, nanomedicine-based drug delivery strategies have been exploited for improving cancer immunotherapy by boosting ICD of the tumor cells. Nanosized drug delivery systems are promising for increasing drug accumulation at the tumor site and codelivering ICD inducers and immune inhibitors to simultaneously elicit the immune response and relieve the ITM. This review highlights the recent advances in nanomedicine-based immunotherapy utilizing ICD-based approaches. A perspective on the clinical translation of nanomedicine- based cancer immunotherapy is also provided.